Program Pendidikan Kecakapan Kerja (PKK) Sarana Digitalisasi Generasi Z Melawan Gagap Teknologi di Lembaga Kursus dan Pelatihan (LKP) Andikon Jatirogo Tuban - Lilis Amriati; Istingadah Istingadah; Popy Nurmaeni (Journal of Innovation and Contribution to Community Service, 2025)
The vocational education program is a process of developing potential, talent, and expertise to make individuals who are proficient in operating computers which are for provision in developing themselves, and the profession, and can help increase job opportunities for the community in a better direction. The vocational education program carried out by LKP ANDIKOM provided various kinds of training and mentoring courses for free such as operating Microsoft Office applications, Word, Excel, and PowerPoint along with graphic designs in the form of Photoshop and CorelDraw. The purpose of this study is to describe the efforts of vocational education through computer technology facilities at the Andikom Jatirogo training and education institution in achieving capacity, talent, and independent business development. Data collection techniques through interviews, observation, and documentation are used as a complement to obtaining data as information material. The results showed that the work skills education program efforts through computer technology facilities carried out by LKP ANDIKON Jatirogo in assisting the improvement of community welfare were carried out with a development framework (enabling) the creation their job opportunities regarding financial management, marketing, and product distribution.